(untitled) (Anclajes, 2026)
In the mid-20th century, artists such as Bob Dylan and the French singer-songwriters came to be regarded as authors thanks to the borrowing of a romantic and literary notion of authorship. This transfer between the arts entails a shift that helps explain the concept of the songwriter as an author. Drawing on Hegelian thought regarding popular song and Adorno’s critique of mass culture, this study argues that this shift illustrates the acceptance of the songwriter as a literary author, a process that was consummated following Dylan’s Nobel Prize. To this end, the study combines a diachronic perspective—which examines the impact of these authors in the 1960s—with a synchronic perspective centered on the analysis of the rockstar in 21st-century novels and his legacy in rap.